Burnout as a Mediator Between Work–School Conflict and Work Outcomes. (October 2016) - Laughman, Courtney; Boyd, Elizabeth M.; Rusbasan, David
Conflict occurring between the roles of work and family has been heavily researched. Recently, however, research has been branching out to study roles beyond work and family. For example, a few researchers have investigated conflict that occurs between the roles of work and school. However, these studies have focused mainly on school and personal outcomes. As such, the present study seeks to contribute to the literature on work–school conflict in two main ways. First, we investigate the relationship between work–school conflict and job outcome variables. Next, we seek to understand the mediating mechanism through which work–school conflict affects job outcomes. Participants in this study were 304 students who completed a survey regarding their attitudes toward work and school. Results were largely supportive of the hypotheses predicting that work–school conflict predicted work outcomes and that burnout mediated these outcomes. Implications for organizations and universities are discussed.